Neuronal excitation upregulates Tbr1, a high-confidence risk gene of autism, mediating Grin2b expression in the adult brain - Chuang, Hsiu-Chun; Huang, Tzyy-Nan; Hsueh, Yi-Ping (Frontiers in Cellular Neuroscience, 2014)
The activity-regulated gene expression of transcription factors is required for neural plasticity and function in response to neuronal stimulation. T-brain-1 (TBR1), a critical neuron-specific transcription factor for forebrain development, has been recognized as a high-confidence risk gene for autism spectrum disorders (ASDs). Here, we show that in addition to its role in brain development, Tbr1 responds to neuronal activation and further modulates the Grin2b expression in adult brains and mature neurons. The expression levels of Tbr1 were investigated using both immunostaining and quantitative RT-PCR analyses. We found that the mRNA and protein expression levels of Tbr1 are induced by excitatory synaptic transmission driven by bicuculline or glutamate treatment in cultured mature neurons. The upregulation of Tbr1 expression requires the activation of both AMPA and NMDA receptors. Furthermore, behavioral training triggers Tbr1 induction in the adult mouse brain. The elevation of Tbr1 expression is associated with Grin2b upregulation in both mature neurons and adult brains. Using Tbr1-deficient neurons, we further demonstrated that TBR1 is required for the induction of Grin2b upon neuronal activation. Taken together with the previous studies showing that TBR1 binds the Grin2b promoter and controls expression of luciferase reporter driven by Grin2b promoter, the evidence suggests that TBR1 directly controls Grin2b expression in mature neurons. We also found that the addition of the calcium-calmodulin kinase II (CaMKII) antagonist KN-93, but not the calcium-dependent phosphatase calcineurin antagonist cyclosporin A, to cultured mature neurons noticeably inhibited Tbr1 induction, indicating that neuronal activation upregulates Tbr1 expression in a CaMKII-dependent manner. In conclusion, our study suggests that Tbr1 plays an important role in adult mouse brains in response to neuronal activation to modulate the activity-regulated gene transcription required for neural p